DIALEKTIKA AGAMA DAN BUDAYA - Poniman Poniman (Universitas Islam Negeri Fatmawati Sukarno, 2015)
Religion as divine guidance was revealed to humans who have had culture. While the culture is essential in the life of a society, as a society however simple, still have a work culture, ethics and taste. When religion comes to this locus there was a dialectic between the two. This dialectic bore variant-variant in religion ie Islam Indonesia, Islam Morocco and so on. More specifically, when the religion (Islam) dialectic with the local culture (local wisdom) will form a distinctive variant of Islam such as: Islam Madura, Islamic Javanese, Malay Muslims and so on. This variant does not mean that religion has been deprived of its purity, but religion was dialectic with culture